2015
DOI: 10.1890/14-2302.1
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling legacy effects from environmental filters of postfire assembly of boreal tree assemblages

Abstract: Disturbance plays a key role in driving ecological responses by creating opportunities for new ecological communities to assemble and by directly influencing the outcomes of assembly. Legacy effects (such as seed banks) and environmental filters can both influence community assembly, but their effects are impossible to separate with observational data. Here, we used seeding experiments in sites covering a broad range of postdisturbance conditions to tease apart the effects of seed availability, environmental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 45 publications
4
53
0
Order By: Relevance
“…Indeed, vegetation legacies after fire affect seed availability and play a pivotal role in shaping patterns of community assembly after fire in these low-diversity boreal forests1213. As Larch forests are becoming increasingly seed-limited in response to intensifying fire regimes, lack of seed may potentially change forests to alternative vegetation-disturbance feedbacks under a future warmer and drier climate (e.g., shrubland or grassland with frequent, high-severity, fires), consistent with conclusions from a field-based study20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, vegetation legacies after fire affect seed availability and play a pivotal role in shaping patterns of community assembly after fire in these low-diversity boreal forests1213. As Larch forests are becoming increasingly seed-limited in response to intensifying fire regimes, lack of seed may potentially change forests to alternative vegetation-disturbance feedbacks under a future warmer and drier climate (e.g., shrubland or grassland with frequent, high-severity, fires), consistent with conclusions from a field-based study20.…”
Section: Discussionmentioning
confidence: 99%
“…Observational and experimental studies have found that fire interacts with tree species’ fire-adaptation strategies, strongly affects seed availability and site condition, and thus plays a dominant role in determining tree recruitment in the boreal forest ecosystem1213. In fire “embracer”-dominated forests, such as those dominated by Picea mariana , Pinus contorta , and Pinus banksiana , fires are typically of intermediate frequency and high severity.…”
mentioning
confidence: 99%
“…These rates are species‐specific and depend in part on seed size: smaller seeds generally require closer proximity to the mineral soil (Hesketh et al., ) due to lower seed reserves to support initial root development (Lazarus, Castanha, Germino, Kueppers, & Moyes, ). Therefore, where organic layer consumption is incomplete, larger‐seeded conifers generally exhibit higher postfire recruitment than smaller‐seeded broadleaved species (Brown, Liu, Yan, & Johnstone, ; Johnstone & Chapin, ; Johnstone & Kasischke, ). Among conifers, black spruce Pic.…”
Section: Demographic Filters Determine Postfire Vegetation Communitiesmentioning
confidence: 99%
“…GLMs have many advantages over standard linear models or regression approaches; in particular, they are more flexible by assuming various families of probability distributions (Guisan et al 2002;O'Hara and Kotze 2010). As the fire activity data had excess zeros, we used a zero-inflated negative binomial generalised linear model (ZINB-GLM) to handle zeros and over-dispersion in the count data (Zeileis et al 2008;Brown et al 2015). For presence and absence data, we used a binomial GLM.…”
Section: Modellingmentioning
confidence: 99%